2021
DOI: 10.3389/fmicb.2021.646302
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiomes of Young Beech Trees Are Distinguished by Organ Rather Than by Habitat, and Community Analyses Suggest Competitive Interactions Among Twig Fungi

Abstract: Beech trees (Fagus sylvatica) are prominent keystone species of great economic and environmental value for central Europe, hosting a diverse mycobiome. The composition of endophyte communities may depend on tree health, plant organ or tissue, and growth habitat. To evaluate mycobiome communalities at local scales, buds, and twigs were sampled from two young healthy mountain beech stands in Bavaria, Germany, four kilometers apart. With Illumina high-throughput sequencing, we found 113 fungal taxa from 0.7 milli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…As a cultivation-independent method it is frequently used to study the diversity and potential function of microbial communities [1][2][3]. Mycobiomes (or microbial fungi) in the phyllosphere of trees have been studied to investigate their association with tree performance related to plant internal and external factors such as plant genotype [4,5], organ specificity [6], and geographic and climatic parameters [7][8][9][10][11][12]. Sequencing protocols and bioinformatic pipelines that are used to dissect metagenome data are also under rapid development [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…As a cultivation-independent method it is frequently used to study the diversity and potential function of microbial communities [1][2][3]. Mycobiomes (or microbial fungi) in the phyllosphere of trees have been studied to investigate their association with tree performance related to plant internal and external factors such as plant genotype [4,5], organ specificity [6], and geographic and climatic parameters [7][8][9][10][11][12]. Sequencing protocols and bioinformatic pipelines that are used to dissect metagenome data are also under rapid development [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Fungal communities in tree foliage are not uniformly distributed or stationary ( Toju et al., 2019 ); their composition is influenced by several factors including host genotype ( Albrectsen et al., 2010b ), growth site ( Siddique et al., 2021 ), seasonal factors ( Albrectsen et al., 2010b ), ontogeny ( Bourassa et al., 2005 ; Boutigny et al., 2013a ), tissue type ( Siddique et al., 2021 ), and host-associated consumers ( Arnold et al., 2003 ; Albrectsen et al., 2010b ; Siddique et al., 2021 ). The mechanisms underpinning these relationships are not fully understood but it has been suggested that both the host’s chemical defense responses ( Ullah et al., 2017 ; Witzell et al., 2022 ) and competition between members of the mycobiome may help shape the microbial community ( Wemheuer et al., 2019 ; Siddique et al., 2021 ). In the present study, we also obtained results suggesting the occurrence of a transition in the composition of the fungal community.…”
Section: Discussionmentioning
confidence: 99%
“…Even if this approach has rarely been applied, to date, in the pollen DNA metabarcoding literature (Table 1), it was specifically developed to distinguish "true signals" from "noise" [102] in molecular biology and could constitute a promising avenue for processing data of pollen DNA metabarcoding. For instance, it has been used in other DNA-based research fields [103,104], such as for eDNA where it is proved to increase the reliability of data [105]. However, it would be promising to investigate how different parametrizations of the ROC approach would impact the estimations of cutting thresholds.…”
Section: Discussionmentioning
confidence: 99%